2020
DOI: 10.1038/s41385-020-0318-2
|View full text |Cite
|
Sign up to set email alerts
|

IL-17A both initiates, via IFNγ suppression, and limits the pulmonary type-2 immune response to nematode infection

Abstract: Nippostrongylus brasiliensis is a well-defined model of type-2 immunity but the early lung-migrating phase is dominated by innate IL-17A production. In this study, we confirm previous observations that Il17a-KO mice infected with N. brasiliensis exhibit an impaired type-2 immune response. Transcriptional profiling of the lung on day 2 of N. brasiliensis infection revealed an increased Ifng signature in Il17a-KO mice confirmed by enhanced IFNγ protein production in lung lymphocyte populations. Depletion of earl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 44 publications
4
31
0
Order By: Relevance
“…The cytokine, IL-17, is a potent driver of neutrophil recruitment and plays a complex role in both initiation and suppressing type 2 inflammatory responses, such as those seen in allergic asthma. 57 A study by de-Oliverira and colleagues investigated the rules governing the localization of IL-17-producing gamma-delta T cells in the airways of mice. 58 Specifically, the authors found that offspring of mice that had been immunized with an antigen, and subsequently developed a specific IgG response, exhibited a reduced number of IL-17 producing gamma-delta cells in the airways.…”
Section: Airway Remodelling In Asthmamentioning
confidence: 99%
“…The cytokine, IL-17, is a potent driver of neutrophil recruitment and plays a complex role in both initiation and suppressing type 2 inflammatory responses, such as those seen in allergic asthma. 57 A study by de-Oliverira and colleagues investigated the rules governing the localization of IL-17-producing gamma-delta T cells in the airways of mice. 58 Specifically, the authors found that offspring of mice that had been immunized with an antigen, and subsequently developed a specific IgG response, exhibited a reduced number of IL-17 producing gamma-delta cells in the airways.…”
Section: Airway Remodelling In Asthmamentioning
confidence: 99%
“…This is in line with a recent observation where intestinal helminth infection was shown to influence lung responses (in the absence of a lung challenge) through IL-17mediated dampening of IFNγ, which consequently enhanced Th2 responses. 6…”
mentioning
confidence: 99%
“…In this issue of Mucosal Immunology, Ajendra et al reveal previously unrecognized ways that IL-17A "multi-tasks" in the lung, to both promote and inhibit Type 2 inflammation, depending on timing and the surrounding inflammatory milieu, using the Nippostrongylus brasiliensis helminth infection model in mice. 1 N. brasiliensis is a hookworm-like parasite that after infecting its host through the skin, migrates quickly through the lung between days 1 and 3 post-infection inducing damage and inflammation, before reaching its final destination, the intestines by days 5-7. The authors show that in this setting, IL-17A expression is rapidly induced in γδ T cells in the lung at day 2, which acts to suppress the production of IFNγ by T cells and NK cells, facilitating the induction of a type 2 response while the helminth passes through the lung.…”
mentioning
confidence: 99%
“…Overall, Ajendra et al 1 presents an exciting new model in which helminth infection-driven IL-17A is central for both the initiation of a Type 2 response, and its subsequent inhibition to help prevent chronic Type 2 inflammation and tissue damage. Suppression of IFNγ expression in the lung appears to be a critical intermediate event, and appears to be a tissue-specific phenomenon.…”
mentioning
confidence: 99%
See 1 more Smart Citation